Lipoma of the Ischiorectal Fossa: A Rare Case Report - Djavan Khubanov; Kamala Gasimova (Caucasian Medical Journal)
Ischiorectal fossa (IRF) masses are uncommon and pose significant diagnostic challenges because of their varied etiologies. This case report presents a rare case of an IRF lipoma in a 55-year-old female patient characterized by a large, benign gluteal mass. Clinical evaluation included imaging with contrast-enhanced magnetic resonance imaging (MRI), which confirmed the presence of a 147x67 mm transverse lipomatous mass extending into the right gluteal fold without malignant features. Surgical resection was performed using the posterior midline approach, which allowed complete tumor removal with optimal cosmetic outcomes. Postoperatively, the patient remained symptom-free, with no recurrence noted after 8 months. This report emphasizes the importance of MRI in the diagnostic process and surgical planning of IRF masses and highlights the rarity and unique characteristics of lipomas in this anatomical location.